Epidemiological, phenomenological, and treatment aspects of trauma and posttraumatic stress disorder in children and adolescents - Seedat, Soraya (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Psychiatry))--University of Stellenbosch, 2005.